Implementation of Family Social-Cultural Function: Introducing Local Culture Among Children 4-6 Years Old in The Village of Literacy, Jakarta - Rohita, Rohita; Amalia, Rizqi Maulida; Jayanti, Asri (Indonesian Journal of Early Childhood Education Studies, 2021)
Introducing local culture to the younger generation, which is carried out on children from an early age, is one way to protect Indonesian culture. It is not eroded by the times. This study aims to determine how parents introduce their local culture to children aged 4-6 years. The method is using qualitative. The research subject is determined using purposive sampling in which subjects are selected based on criteria families with children aged 4-6 years, living in RT 08 RW 08 and willing to become respondents. Based on criteria is obtained subject as many as 10 people. Data collection was carried out by an in-depth interview method using a questionnaire distributed to parents. This is done because physical and social distancing is still being applied. Data analysis was performed using the Miles and Huberman model, including data reduction, data display, and data verification. Presentation of data is by displaying tables, diagrams, and narratives to strengthen understanding. The results showed that parents introduced local culture to their children in the form of regional food, folk songs, and regional games using any media. Recommendations are given to the stakeholders that should improve the number of related local cultural reference books.